A inclusão dos transtornos mentais como doença relacionada ao trabalho: discursos sobre as dificuldades de reconhecimento dos nexos causais - Silva, Rafaela Aparecida Cocchiola (2011)
This work had the intention to understand the mental disorders in political discussions focused on the health of the worker and the inclusion of this diagnostic category as a group of disease caused or triggered by conditions and labor relations. The proposal is based on theoretical and methodological perspective in the Social Discursive Psychology constructionist strand where the research assumes that knowledge is a collective enterprise, and thus a social practice. The theme of mental disorders in a professional context is an old subject in specialized literature, it is possible to find texts were mental disorders such as depression resulting from the use of substances harmful to health, were described in Ancient times. We can also find studies on mental disorders in the 1950s in France on the neurosis of the telephone. However, in Brazil, mental disorders were recognized as a group of diseases related to work only in 1999 by Decree 3048, which were divided in a set of 12 diagnostic categories and their etiologic agents or risk factors of occupational origin. It is argued that the inclusion of mental disorders and work-related illness stems from a confluence of factors which have allowed the expansion of the concept of health, seen not only as the absence of disease. Another important fact were the advances around the social prejudice against the subject of mental disorders and refining ways to recognize the causal connection based on the methodology of the Nexus Technical Epidemiological Welfare (NTEP), implemented by Social Security in 2007 for granting welfare benefits. The entry of mental disorders in policies on workers' health was examined considering the difficulties in recognizing the link between work and disease from the perspective of the three Conferences National Occupational Health. The debate about mental disorders was included on the agenda for health policy geared to the employee specifically in the 2nd CSNT held in 1994, and discussed that the difficulties of this recognition by both unionists and workers, were related to the peculiar characteristics of mental illnesses viewed as a source of individual illness and not as a consequence of the conditions and labor relations. Such a conception of individual determinants of mental disorders permeated the difficulties of recognizing the causal relationship, understood as the object of disputes and set of interests among the actors involved in the recognition of this issue as a work related disease, taken here as forms of regulation by biopower